The impact of green strategy formulation processes on the adoption of green strategy areas at the functional level - حسين السعيدي يعرب عدنان; عبدالله سلوان ظافر (Journal of Economics and Administrative Sciences, 2020)
The research aims at demonstrating the role of the formulation of the green strategy in adopting the areas of the green strategy at the level of jobs in the municipal institutions in the province of Babylon, specifically the Directorate of the municipality of Hilla. The most important areas related to the green strategy were highlighted directly or indirectly, after the indicators of environmental damage emerged from the actions of companies and institutions. The research included a sample size of 222 individual of municipal institutions with different job titles and specializations between the technical and administrative and different levels of academic achievement within the institutions within the Ministry of Construction, Housing and Municipalities, Ministry of Planning as well as the provincial council of Babylon, which is related to the work of municipal institutions. Through the research tool, the questionnaire distributed to the research sample was homogeneous and harmonious and had high answers. The research concludes with important recommendations for the adoption of the Foundation as a green strategy, which included the focus on the formulation of green strategies and follow-up and the importance of the participation of the administration as well as the need to pay attention to the planning of green infrastructure and make it a strategic priority.